A case report of postoperative VRSA enteritis: Effective management of rifampicin for vancomycin resistant Staphylococcus aureus enteritis after esophagectomy and colon reconstruction. (2018) - Okada, Naoya; Fujita, Takeo; Kanamori, Jun; Sato, Ataru; Horikiri, Yasumasa; Sato, Takuji; Fujiwara, Hisashi; Daiko, Hiroyuki
Highlights: In this case report, this patient underwent esophagectomy, total resection of the gastric remnant, and colon reconstruction, and it is likely that methicillin-resistant Staphylococcus aureus (MRSA) from the upper airway system, which is not exposed to gastric acid, proliferated in the interposed colon and resulted in MRSA enteritis. Vancomycin-resistant Staphylococcus aureus (VRSA) arises from MRSA through the transfer of vancomycin resistant genes on the vanA operon to S. aureus. This case report describes the potential for rifampicin to be used as an effective treatment choice for postoperative VRSA enteritis. Abstract: Introduction: Vancomycin is one of the most widely used antibiotics for the treatment of serious infectious caused by methicillin-resistant Staphylococcus aureus (MRSA). However, reduced susceptibility of S. aureus to vancomycin has been observed in recent years. We report on a case of vancomycin resistant methicillin-resistant Staphylococcus aureus (VRSA) enteritis after colon reconstruction followed by esophagectomy and completion gastrectomy, with extended lymph node dissection for esophageal squamous cell carcinoma. Presentation of case: A 66-year old male was referred to our hospital for esophageal carcinoma of clinical stage T3 N0 M0, Stage IIA. From the postoperative day 3, the patient reported heavy watery stools on more then 10 occasions and high fever, and was diagnosed with the methicillin-resistant Staphylococcus aureus (MRSA) enteritis. We administered vancomycin to treat the enteritis, although a subsequent stool culture indicated VRSA instead of MRSA. Rifampincin treatment was initiated and the patient's symptoms improved. Discussion: In this case report, this patient underwent esophagectomy, total resection of the gastric remnant, and colon reconstruction, and it is likely that methicillin-resistant Staphylococcus aureus (MRSA) from the upper airway system, which is not exposed to gastric acid, proliferated in the interposed colon and resulted in MRSA enteritis. Conclusions: Rifampicin represents an effective treatment strategy for postoperative VRSA enteritis.